Aturan Main Pada Keselamatan Kerja Ojek Online: Studi Kasus di Pt. Gojek Indonesia Cabang Surabaya - Salsabila, Arini Alfi; Kristina, Anita (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
This study analyzes the rules that govern the protection provided by companies both wage protection for the consequences of the magnitude of the risk and protection from the risk of workplace accidents. A qualitative case study approach is used in this research. Data collection through in-depth interviews with informants namely representatives of the management of PT. Gojek Indonesia Surabaya branch and representatives of online motorcycle taxi workers who have worked for at least three months. The results of this study found that companies build and maintain institutional arrangements through rules, both formally and informally (agreements). The wage system is carried out by the driver doing the order service and also a bonus system from the company. Workers also have rights and obligations and the company will provide sanctions and rewards. The company's efforts to reduce the risk of work accidents are also related to the company's commitment through insurance facilities, the company also cooperates with the police regarding the safety of workers and passengers, and also provides welfare programs. The conclusion in this study that the safety of online motorcycle taxi workers is given by the company in the mechanism of institutional rules in the mechanism of work protection.